Design and Realization of Circular Microstrip Antenna as Wifi Receiver Antenna Using Double Patch Array Method with Slot - Rahman, Ahmad Aulia'ur (Universitas Medan Area, 2019)
Wifi technology is a means to obtain information quickly, to strengthen the role of the signal, an antenna is needed because the antenna serves as a means for transmitting and receiving electromagnetic waves which are contained signal information. Mikrostrip antenna has a characteristic that is small, light, thin, easily fabricated, and can be used at a great distanceIn the use of wifi antenna require a relatively small shape and a cheaper prize. One of the antena on that specification is a microstrip antenna. By using 2 circular array method, the microstrip antenna can improve the wifi signal and wider on bandwidth. In this final project will be designed and created microstrip antenna with the 2 patches ccircular array methodwith slot that will be used as a wifi receiver. The results of the antenna microstrip rectangular 2 patches measurement indicating that it can work optimally on 2.406 GHz frequency, on a value of return loss ? 22.90 dB, a value of VSWR 1.160, a value of bandwidth 0. 1035 GHz, and a value of gain 14.95 dBi.